Standard Agreement at PT Finansia Multi Finanse (A Review of Law Number 8 Year 1999 concerning Consumer Protection) - Mardia Ibrahim; Dahlai Hasim (Faculty of Law, Khairun University, 2021)
Standard Agreement at PT Finansia Multi Finanse (A Review of Law Number 8 Year 1999 concerning Consumer Protection) This study aims first to determine the implementation of the Standard Agreement at PT Finansia Multi Finanse in Ternate City Second To find out the Standard Agreement Settlement in the event of default by parties Creditors This type of research is empirical normative, because what is being studied is a problem regarding matters that are juridical and the existing facts regarding empirical normative research methods, because what is being studied is a problem regarding matters that are juridical and the existing facts regarding juridical review of the implementation of the agreement. standard at PT Finansia. And the Standard Agreement Settlement in the event of default by the debtor party in Ternate City, while normative determines what is allowed and what cannot be regulated in the Civil Code. Based on the results of research and discussion, it can be concluded that First, the implementation of the Credit Agreement at PT Finansia Kota Ternate, from the last 5 months in 2020 there has been an increase, it can be seen that customers who make credit loans in the form of money or other electronic goods increase every month until the time This is because every customer who makes a credit loan at PT Finansia Kota Ternate is not convoluted so that from May to September 1743 customers made credit loans, or up to 98%. Second The legal consequence is that if there is default at PT Finansia Kota Ternate, the last 5 months in 2020 reached 10 customers or 0.5.5% of 1743 customers, the customer as a debtor has the authority to carry out and maintain the customer's credit loan items if PT Fainansia does default in accordance with the applicable law.